Modeling of Lightning Strike Events, and it’s Correlational with Power Outages in South-West Coast, Nigeria - Melodi A. O. A. O.; Olayinka Matthew Oyeleye (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper aimed to model lightning strike events and evaluate its correlation with power outages in a Nigerian power distribution system. A specified coastal distribution network of southwest Nigeria was selected as a case study. Zone-specific records of cloud-to-ground lightning strikes for 84 months were obtained from the Nigerian Meteorological Agency (NiMet); records of power outage frequencies and durations for 36 months were obtained at the substations of the selected distribution network. Using numerical statistical analysis techniques, lightning activity in the system area were characterized in relative frequency terms, and correlation statistics were evaluated and analyzed for power outages and lightning events on the 11kV, 33kV, and 132kV voltage levels. An analysis of the results shows that the modelled lightning strike events patterns are closely related but the expected frequencies vary from one zone to another; and there is correlation between lightning strike and power outages in the distribution networks, which is strong and positive at the 33 kV and 132 kV circuits. In essence, the results provided salient information, useful for power systems lightning protection review, management and planning in the area.